Influencia del tiempo y la concentración inicial en la remoción de soluciones ideales del insecticida metomilo utilizando la microalga Chlorella sp. - Alfaro Flores, Astrid Georgette (2019)
The water bodies pollution by pesticides due to their excessive use in agriculture is one of the biggest environmental problems to face in our country. In this research, microalgae cultivated at the National University of San Agustín de Arequipa, (species Chlorella sp.) were used, which were subsequently cultivated in aerated bioreactors constantly on a laboratory scale. The experimental system consisted of 250 ml volume Batch bioreactors, with an air flow of 2L/min, in which the Microalgae solution was contacted for five days, with ideal solutions of methomyl, with initial concentrations of 10, 25 and 40 ppm. Two treatments were performed separately, with three replicas each one. The first with microalgae harvested in its exponential phase of growth and the second with microalgae harvested in the stationary phase. The results obtained shows a maximum removal of 56.34%, which was reached using an initial concentration of methomyl of 25 pppm and using microalgae in the exponential phase of growth. It is concluded that microalgae are capable of removing the methomyl insecticide from water, this being an economically viable and environmentally friendly alternative